False-Positive Results of SARS-CoV-2 RT-PCR in Oropharyngeal Swabs From Vaccinators - Kong, Xiang-Qi; Wang, Yong-Jing; Fang, Zan-Xi; Yang, Tian-Ci; Tong, Man-Li (Frontiers in Medicine, 2022)
Real-time reverse transcription polymerase chain reaction (RT-PCR) is the gold standard for diagnosing coronavirus disease 2019 (COVID-19). However, RT-PCR may yield false-positive results, leading to unnecessary countermeasures. Here, we report a “positive” nucleic acid test on a 10-pooled sample during routine screening that caused many adverse societal effects, and financial and resource losses. However, they were subsequently determined to be case of vaccine contamination. This case study increases awareness of false-positive RT-PCR results for SARS-CoV-2, especially when participants are vaccinators. Moreover, it could provide relevant suggestions to prevent recurrence of such incidents.